Immigrant and native black college students : social experiences and academic outcomes - Thomas, Audrey Alforque, 1974- (New Americans (LFB Scholarly Publishing LLC), 2014)
The literature suggests that African Americans (native Blacks) differ from Black immigrants and children of Black immigrants (immigrant Blacks) in their educational outcomes. Thomas contributes to this growing body of work, showing through regression analyses and interview data, similarities in college experiences and outcomes. There is a unique Black college experience that transcends family immigration history. Social integration and intellectual integration into the university is different for Black students as compared to White, Asian, and Chicano/Latino students.